Urgensi Mengucapkan Dua Kalimat Syahadat dalam Kesehatan Pasien Muslim - Faiha, Anisah; Meiyanda, Azzah Abidah; Nadira, Fahmaan Hafizh; Amiruddin, Muhammad (Maliki Interdisciplinary Journal, 2025)
This study examines the urgency of reciting the Shahada in the context of Muslim patients’ health, particularly in the final phase of life, which often causes high emotional and spiritual stress. This study uses a qualitative approach with library research methods that combine theological, psychological, and health analysis to comprehensively understand the role of the Shahada. Data sources include the Quran, Hadith, classical Islamic literature, and contemporary research on palliative care and spiritual support for Muslim patients. The results of the study indicate that reciting the Shahada is not merely a religious ritual, but a manifestation of steadfast faith that can bring a sense of peace, reduce existential anxiety, and strengthen acceptance of illness and death. Furthermore, the Shahada has been shown to play an important role in forming a spiritual coping mechanism that helps patients adjust to the psychological stress of chronic or terminal illness. From a medical perspective, the spiritual calm resulting from reciting the Shahada contributes to emotional stability and an improved quality of life for patients. The results also emphasize the need to integrate spiritual support into modern healthcare services through collaboration between medical personnel and religious leaders. Thus, strengthening the spiritual aspect through the two sentences of the shahada is an important part of holistic care that not only nourishes the body, but also calms the soul and prepares the patient for a dignified death according to Islamic teachings. spiritual aspects through syahada is crucial in improving the quality of life and ensuring a dignified death for Muslim patients.